Pemetaan Kitab Hadis Di Pesantren Sumatera Selatan (RIWAYAH, 2018)
Based on the phenomenon of the use of Hadist's books referenced by the pesantren, has not provided the maximum information related to the existence of the hadith book in the pesantren in South Sumatra. Whereas the Hadith is a source of Islamic law that became the reference of the kyai or the leadership of pesantren in disseminate Islam. If the existence of the reference books is unknown or unfounded, then what book do they hold in preaching and preaching the word Islam. This study shows the use of hadist books and methods of learning hadith. Data collection is done through documentation either in form of book or internet also interview with pesantren board and alumni of pesantren. The study found that the study of Hadith in Al-Ittifaqiah Pesantren based on al-Azhar curve. The main book used is the book Bulughul Maram by Ibn Hajar al-Asqalani. The supporting book is Arba'in by Imam al-Nawawi. Book of Hadith at Islamic Boarding School Nurul Islam Seribandung, using a lot of references hadith books. Among the books that have been used in PPNI since 1938 to 1984 are books written by religious teachers and kyai PPNI in Malay language (with Arabic Pegon script). Since 1984, the PPNI curriculum has been changed following the national curriculum of the hadith books of Arba'in and Jawahir al-Bukhari for the Tsanawiyah level and the book of Bulughul Maram's hadith for the level of Aliah. Book of Hadith at Pondok Pesantren Raudlatul Ulum Sakatiga in 2003 until now in 2017, the book still used in this pesantren Bulughul Marram.